An Analysis Ma’rimpa Salo As A Traditional Culture In Sinjai Regency (A Cultural Approach) - Andi Rukayah; Burhanuddin Burhanuddin; Rezki Fadilah (Fakultas Sastra - Universitas Muslim Indonesia, 2018)
The purpose of this study is to know the local culture in Sinjai. As we see today is the technology and foreign cultures that keep us from the life and culture of our ancestors gradually been worn. The method used in this research is qualitative descriptive method that given images or facts. The writer needed library research, field research, observation, interview, and documentation to support the data. Marimpa Salo is dispels activities from upstream to the mouth of the fish is done in two villages namely Sanjai Village and Bua Village, both of which are mediated by Appareng River. This tradition has been carried out in the time of Bulo Bulo kingdom are still preserved Sinjai district until now. The results of this study are expected to be fruitful thought